Experiences of Rohingya's journey to Malaysia: Smuggled or trafficked - Wan Yusoff, Wan Mazwati (2017)
Two protocols on human smuggling and human trafficking under United Nation Convention against Transnational Organized Crime explicate the differences between human smuggling and human trafficking. The popular assumption on human smuggling and trafficking is that is operated by organized criminal groups. Within this framework, this study attempts todetermine how the Rohingas entered Malaysia, their experiences during the journey to Malaysia and who were the agents involved in transporting them into Malaysia. This preliminary study provides literature and empirical data on human smuggling and trafficking which is wanting. This is significant for further action by the policy makers as well as providing valuable information for social workers when dealing with the Rohingya refugees. Qualitative research method was employed to conduct the study. The participants were 45 Rohingya's who lived in Ampang, Selangor. They were interviewed in sharing of experience sessions to collect data. The data were transcribed and analyzed qualitatively. the findings revealed harrowing experiences of being transported from one place to another a very inhuman condition and confirmed the assumption that the Rohingya's were both smuggled and trafficked into Malaysia with exorbitant fees while the agents were not necessarily from big organized criminal groups.